2021
DOI: 10.3390/nu13082670
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Levels in Human Milk Are Related to Maternal Nutrition and Infant Health and Growth

Abstract: Background: Osteopontin (OPN) is a glycosylated phosphoprotein found in human tissues and body fluids. OPN in breast milk is thought to play a major role in growth and immune system development in early infancy. Here, we investigated maternal factors that may affect concentrations of OPN in breast milk, and the possible associated consequences for the health of neonates. Methods: General characteristics, health status, dietary patterns, and anthropometric measurements of 85 mothers and their babies were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 60 publications
(89 reference statements)
2
18
0
Order By: Relevance
“…In addition to HMOs, the levels of milk protein and lipids can also be affected by many maternal factors, including smoking, BMI, birth route, pregnancy weight gain, and energy intake during lactation. For example, Aksan et al ( 68 ) have detected significant correlations between body weight, length, and head circumference, respectively, and OPN levels after one ( r = 0.442, p = < 0.001; r = −0.284, p = < 0.001; r = −0.392, p = < 0.001) and 3 months ( r = 0.501, p = < 0.001; r = −0.450, p = < 0.001; r = −0.498, p = < 0.001) of lactation.…”
Section: The Sialylated Components In Milkmentioning
confidence: 99%
“…In addition to HMOs, the levels of milk protein and lipids can also be affected by many maternal factors, including smoking, BMI, birth route, pregnancy weight gain, and energy intake during lactation. For example, Aksan et al ( 68 ) have detected significant correlations between body weight, length, and head circumference, respectively, and OPN levels after one ( r = 0.442, p = < 0.001; r = −0.284, p = < 0.001; r = −0.392, p = < 0.001) and 3 months ( r = 0.501, p = < 0.001; r = −0.450, p = < 0.001; r = −0.498, p = < 0.001) of lactation.…”
Section: The Sialylated Components In Milkmentioning
confidence: 99%
“…Indeed, the vitamin D content in the milk was higher in the 1989 cohort than in a cohort sampled in 2016–2017, possibly due to limited sunlight exposure in the recent mothers [ 15 ]. Furthermore, it was reported that the OPN content was lower in the breast milk samples from mothers who delivered via a C-section than from mothers who delivered vaginally [ 24 ]. However, data from the 2013 cohort indicated that the OPN levels were significantly lower in C samples (3–5 days postpartum) from women who delivered vaginally than from women who delivered via a C-section; no differences in the MM samples were noted between the two groups (22–28 days postpartum ( Table S2 )).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the proportion of pregnant women undergoing C-sections is steadily rising in Japan [ 25 ]. A previous study revealed that the OPN levels in breast milk (3 months postpartum) were affected by maternal background characteristics, such as dietary intake (especially energy and fiber intake), BMI, and smoking; in particular, higher OPN levels were found in mothers who delivered vaginally than in those who delivered via a C-section [ 24 ]. Oxytocin promotes the expression of the OPN gene [ 26 ]; its expression is higher during vaginal births than during C-sections [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the biological fluids, the abundance of osteopontin is at a varied level, but thousand-fold lesser than the current detection, and in human milk, the range is 99.7-266.2 μg/mL. 43,44 It shows that the current detection levels can be utilized for determining osteopontin defects in biological fluids.…”
Section: Identification Of Osteopontinmentioning
confidence: 93%